Institutional Violence Against Users of the Family Law Courts and the Legal Harassment Scale - Clemente, Miguel; Padilla-Racero, Dolores; Espinosa, Pablo; Reig-Botella, Adela; Gandoy-Crego, Manuel (Frontiers in Psychology, 2019)
The term harassment is often used to refer two contexts, the workplace and school, but not the legal system itself. Long drawn-out litigation in the Family Law Courts often produces a surreptitious phenomenon of violence towards one of the litigating parties, who become victims of the legal system itself. The aim of this study was to determine whether legal harassment could be detected and measured in the Spanish Justice System using an innovative Legal Harassment Scale (LHS). This hypothesis was substantiated by the data obtained using a new 32-item psychometric instrument with a global index: the Legal Harassment Scale (LHS), consisting of four factors: Direct Aggression, Procedural Harassment, Personal Contempt, and Manipulation of Reality. The estimated reliability and validity of the LHS was satisfactory, both in terms of the global score, and for each of the four factors distributed along the normal curve. The results of this study are discussed in terms of the limitations of the study and in relation to future lines of research aimed at ensuring that the legal system respects and safeguards the rights of the parties involved in litigation, and that no party falls victim to legal harassment.